Isolasi dan Pengklonan Fragmen cDNA Gen Penyandi H+-ATPase Membran Plasma dari Melastoma malabathricum L. - , Muzuni; Didy Sopandie; Utut Widyastuti Suharsono; , Suharsono (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
Melastoma malabathricum L. grows well in acid soil with high level of soluble aluminum. One of the important proteins in the detoxifying acid and aluminum stress is a plasma membrane H+  -ATPase protein encoded by PMA gene. The objective of this research was to isolate and clone the cDNA fragment of MmPMA encoding plasma membrane H+ -ATPase from M. malabathricum L. By reverse transcription, total cDNA had been synthesized from the total RNA as template. The fragment of MmPMA  cDNA  had been successfully isolated by PCR by using total cDNA  as  template and PMA primer designed from conserved region for corresponding gene. This fragment had been successfully inserted into pGEM-T Easy and the recombinant plasmid was successfully introduced into E. coli DH5". Nucleotide sequence analysis showed that the length of MmPMA fragment is 806 bp encoding 268 amino acids. Local alignment analysis based on nucleotide of mRNA showed that MmPMA fragment was 81% identical to part of PMA of Sesbania rostrata, Juglans regia, and Prunus persica. Based on deduced amino acid sequence, MmPMA was 94% identical to part of PMA of Juglans regia; 93% to PMA of S. rostrata, and Arabidopsis thaliana. MmPMA fragment has phosphorylation intermediate domain (DKTGT) and ATP binding domain (KGAP, DPPR, MITGD, and GDGVN).   Keywords: isolation, Melastoma malabathricum L., MmPMA fragment, sequencing